The French curse? On the puzzling economic consequences of French colonization - Andreas Bergh; Guenther Fink (Research Institute of Industrial Economics (IFN), 2018)
More than 50 years after independence, the majority of countries in Sub-Saharan Africa remain poor with limited rates of economic growth. One of the most striking features of economic development on the sub-Saharan subcontinent is the remarkably poor performance of French colonies relative to British ones. While British and French colonies had similar GDP per capita shortly after independence, their economic trajectories have increasingly diverged, with particularly large gaps in the post-2000 period. Neither measures of human capital, geography nor measures of institutional quality appear to explain this gap, suggesting that colonialism affected deeper societal factors that are crucial for economic growth but that are not captured in standard macroeconomic variables.?
Keywords: F54; F63; O43; 330; Growth; Development; Colonies; Institutions